New species and new records of Chaetophloeus LeConte (Coleoptera: Curculionidae: Scolytinae) from Mexico - Burgos-Solorio, Armando; Atkinson, Thomas H. (Zootaxa, 2022)
Three new species of the genus Chaetophloeus LeConte are described from Central Mexico: Chaetophloeus psittacanthi Burgos and Atkinson, sp. nov., C. woodi Burgos and Atkinson, sp. nov., and C. zapotecanus Burgos and Atkinson, sp. nov. A new sexually dimorphic character, the fifth abdominal ventrite, is discussed. Chaetophloeus heterodoxus (Casey) is reported from Mexico for the first time. There are now 17 species of this genus known from Mexico. Significant new distribution and host records for eight species other than the new ones are included.